1996
DOI: 10.1037/0021-9010.81.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive complexity and the perceived dimensionality of pay satisfaction.

Abstract: This study explored the possibility that cognitive complexity can account for differences in the number of perceived dimensions with which individuals conceptualize pay satisfaction, as measured by the Pay Satisfaction Questionnaire. Using 2 independent samples of 1,969 certified teachers, it was found that mean group differences in cognitive complexity may account for the differences previously found in the literature. It was suggested that additional basic research be performed on how individuals conceptuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 26 publications
3
62
0
Order By: Relevance
“…For example, the four dimensions originally proposed by Heneman and Schwab (1985) were supported by DeConink, Stilwell, and Brock (1996); Judge (1993); and Judge and Welbourne (1994). Yet researchers such as Ash, Bretz, and Dreher (1990); Carraher and Buckley (1996);and Scarpello et al (1988) found that the number of pay satisfaction dimensions measured by the PSQ may be fewer than four, depending on the nature of sample. The independence of the pay raise dimension in H. G. Heneman and Schwab's (1985) PSQ has been particularly in question.…”
Section: Self-efficacy Performance and Pay Satisfactionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, the four dimensions originally proposed by Heneman and Schwab (1985) were supported by DeConink, Stilwell, and Brock (1996); Judge (1993); and Judge and Welbourne (1994). Yet researchers such as Ash, Bretz, and Dreher (1990); Carraher and Buckley (1996);and Scarpello et al (1988) found that the number of pay satisfaction dimensions measured by the PSQ may be fewer than four, depending on the nature of sample. The independence of the pay raise dimension in H. G. Heneman and Schwab's (1985) PSQ has been particularly in question.…”
Section: Self-efficacy Performance and Pay Satisfactionmentioning
confidence: 93%
“…The other item, "Influence my supervisor has on my pay," consistently loaded on the pay administration dimension. Carraher and Buckley (1996) showed that in some samples the three-factor model without pay raise dimension was supported. From these findings and other reviews (e.g., Fong & Shaffer, 2003;Judge & Welbourne, 1994), it is evident that there is no unequivocal, commonly agreed-upon number of dimensions, although the PSQ clearly emerges as the preferred measure.…”
Section: Self-efficacy Performance and Pay Satisfactionmentioning
confidence: 95%
“…We consider here whether pay level satisfaction and pay system satisfaction have different effects; however, we do not expect these constructs to be unrelated. Prior research on other types of pay satisfaction invariably shows the components to be distinct but related (see, for example, Carraher and Buckley, 1996;Heneman and Schwab, 1985;Heneman et al, 1988;Huber et al, 1992;Judge and Welbourne, 1994;Scarpello et al, 1988).…”
Section: Study 1 Hypotheses and Modelmentioning
confidence: 97%
“…Based on their review of the empirical studies available at that time, they conclude that ''cognitive complex perceivers take more information into account and form more well-rounded impressions than less complex perceivers'' (Streufert & Swezey, 1986, p. 31). Carraher and Buckley (1996) used the Role Concept Repertoire test to measure cognitive complexity and assess its relationship to the structure of a battery of job satisfaction items. They divided their sample of approximately 2000 teachers into 20 subgroups that were formed on the basis of the cognitive complexity percentile scores (five percentiles in each group).…”
Section: Literature Reviewmentioning
confidence: 99%